Investigation of the Effects of Ghrelin and Kisspeptin Levels in Liver Tissue of Rats Fed with High Fructose Diet -A Histological Study - Ahmet TÜRK; Abdullah KARADAĞ; Büşra ZENCİRCİ; Yusuf ÖZAY; Osman GÜLER (Ahi Evran Medical Journal, 2023)
Purpose: High fructose corn syrup (HFCS) is used commonly in the food industry and has been associated with various diseases including obesity, diabetes and fatty liver. Ghrelin, an orexigenic hormone with widespread receptors in many tissues, exerts various central and peripheral effects. Food intake may reduce its synthesis. Kisspeptin plays a major role in reproductive hormones and its receptors are expressed in tissues with high metabolic activity, such as the liver. This study aims to investigate the effects of HFCS consumption on liver tissue and its relationship with Kisspeptin and Ghrelin levels.